An assessment of contact and laser-based scanning of rock particles for railway ballast - Jerónimo, P.; Resende, R.; Fortunato, E. (Transportation Geotechnics, 2020)
Performance of traditional railway structure depends significantly on the behaviour of its support layers, particularly the ballast. This layer’s rock particles are selected to ensure high mechanical strength, but traffic and mechanical maintenance break and wear the particles. Consequently, the layer incurs permanent deformations that degrade its strength and increase deformability and permeability. Particle physical characteristics, in particular those related to size and shape, influence their fragmentation and wear and must be studied accordingly. In addition, structural numerical models that represent individual particles, such as the discrete element method, have been increasingly used to model the infrastructure and therefore detailed geometrical characterization in the form of 3D digital models of the particles are necessary. This work contributes to this goal by investigating a contact-based cost-effective method that digitizes particle form and allows the determination of their geometric parameters. This method is described, compared with well-established laser scanning technique and then applied to study degradation of particles in Los Angeles and microDeval fragmentation tests.